2020
DOI: 10.1002/glia.23835
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic response to inflammation in astrocytes is regulated by nuclear factor‐kappa B signaling

Abstract: Inflammation and metabolism are intrinsically linked with inflammatory stimuli inducing metabolic changes in cells and, in turn, metabolic capacity determining cellular inflammatory responses. Although well characterized in peripheral immune cells there is comparatively less known about these “immunometabolic” responses in astrocytes. In this study, we tested the hypothesis that the astrocytic inflammatory response driven by nuclear factor‐kappa B (NF‐κB) signaling is dependent on glycolytic metabolism. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
3
24
1
Order By: Relevance
“…In our human cells, we have observed an increase in NFκB gene expression after TNFα and IL1β exposure ( Figure 2 B) that also induced an increase in glycolysis and a reduction in oxidative phosphorylation ( Figure 6 ). These results support, for the first time in human cells, the increase in glycolysis during astrocytic activation, and suggest a possible link between NFκB signaling and glycolysis, similarly to that in mice [ 53 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our human cells, we have observed an increase in NFκB gene expression after TNFα and IL1β exposure ( Figure 2 B) that also induced an increase in glycolysis and a reduction in oxidative phosphorylation ( Figure 6 ). These results support, for the first time in human cells, the increase in glycolysis during astrocytic activation, and suggest a possible link between NFκB signaling and glycolysis, similarly to that in mice [ 53 ].…”
Section: Discussionsupporting
confidence: 75%
“…Transcription factors of the NFκB family are considered not only as central regulators of immune and inflammatory responses, but are also directly linked with energy metabolism regulation [ 52 ]. A very recent study performed on isolated primary mouse astrocytes suggested that the astrocytic inflammatory response driven by nuclear factor kappa B (NFκB) signaling is dependent on glycolytic metabolism [ 53 ]. In our human cells, we have observed an increase in NFκB gene expression after TNFα and IL1β exposure ( Figure 2 B) that also induced an increase in glycolysis and a reduction in oxidative phosphorylation ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another in vitro study of diabetes, recurrent hypoglycemic phases lead to a shift from glucose metabolism to fatty acid oxidation in human primary astrocytes (Weightman Potter et al 2019 ). The same effect was shown after prolonged inflammation induced by LPS stimulation in astrocytes in vitro (Robb et al 2020 ). In addition, XBP1 regulates components of the glucose metabolism and lipogenesis.…”
Section: Discussionsupporting
confidence: 66%
“…Preventing astrocyte inflammation through nuclear factor-kappa B (NF-κB) inhibition in mice astrocytes for example, has been shown to be beneficial by; reducing glial scarring in spinal cord injury; increasing glucose tolerance and promoting energy expenditure; and increasing glucose uptake and glycolytic capacity. Moreover astrocytic glycolytic inhibition by 2-deoxyglucose has recently been shown to significantly reduce LPSinduced cytokine release and NF-κB phosphorylation [32][33][34]. There is also emerging evidence of a link between astrocyte lipid signalling and the metabolic inflammatory response which will be discussed in section 2.…”
Section: Inflammationmentioning
confidence: 95%